Documentation of flora of Rara lake and adjoining areas in mid-western region of Nepal - Basnet, BK (Banko Janakari, 2013)
Rara National Park is the smallest national park of the country. It is rich in floral and faunal diversity. Rara is one of the sacred lakes and is listed as a Ramsar site. The aim of the study was to compile the representative flora of Rara lake and to present status of available vegetation. The research used both primary and secondary sources of data. Field visit was conducted in June, 2010 during which more than 300 plant specimens were collected. The secondary data were collected from Rara and adjoining area like Gamgadi. These data were thoroughly analyzed to understand the composition of vegetation. The study revealed the existence of about 224 flowering plant species in the area, under 173 genera and 67 families. Compositae was found to be the largest family (21 species and 17 genera) followed by Rosaceae (19 species and 10 genera). DOI: http://dx.doi.org/10.3126/banko.v21i1.9063 Banko Janakari, Vol. 21, No. 1 2011; 41-47